Recent developments in land tenure law in Eritrea, Horn of Africa - Castellani, Luca G. (Land Tenure Center, University of Wisconsin-Madison, 2000)
After a historical sketch of the evolution of land tenure systems in the Eritrean highlands, this paper describes the main features of the new Eritrean land law and its operative assumption that the legislation is meant to extend state control over land. The legal devices employed by the law are widely used in sub-Saharan Africa (and were largely inspired by colonial policies). The State of Eritrea frequently asserts that its recent independence gives it the opportunity to learn from other developing countries' mistakes and to avoid them. The basic patterns of the new land law, however, are common to the rest of Africa, notwithstanding the evident poor results. The central government wants its control to be widespread and pervasive. The fight against traditional social groups controlling land, at least in the highlands, is severe. Apart from a formal repeal of customary law, the state's acquisition of the power to modify village boundaries according to a scheme already completed at higher administrative levels and to introduce equal rights on land for women entails a disruption of the villages' social identity. Mandatory state control over landed property in Eritrea is, as usual, motivated by the necessity to address higher social needs. The ultimate intent, of course, is that the evolution from communal property to state property will eventually result in the widespread introduction of individual property once a sufficient level of economic development is achieved. This unfavorable attitude toward communal property is not supported by the evidence, which shows that, in fact, efficient land management can be obtained through renovation of traditional institutions.
iii, 15 p.
Keywords: Land tenure Eritrea; Land tenure Government policy Eritrea; Land tenure Law and legislation Eritrea; Customary law Eritrea; Land reform Eritrea; Tenure types, Traditional Eritrea